Tetramethylpyrazine reverses high-glucose induced hypoxic effects by negatively regulating HIF-1α induced BNIP3 expression to ameliorate H9c2 cardiomyoblast apoptosis - Liu, Shih-Ping; Shibu, Marthandam Asokan; Tsai, Fuu-Jen; Hsu, Yuan-Man; Tsai, Chang-Hai; Chung, Jing-Gung; Yang, Jai-Sing; Tang, Chih-Hsin; Wang, Shulin; Li, Qiaowen; Huang, Chih-Yang (Nutrition & metabolism, 2020)
Diabetic patients are highly vulnerable to hypoxic injury, which is associated with hypoxia induced BNIP3 expression that subsequently activate apoptosis. Our previous research show that Tetramethylpyrazine (TMP), a food flavoring agent, represses the hypoxia induced BNIP3 expression attenuate myocardial apoptosis. In this study, we evaluate the effect of TMP to provide protection against hypoxia aggravated high-glucose associated cellular apoptosis. The cytoprotective effect of TMP against high glucose induced cellular damages was determined on embryo derived H9c2 cardiomyoblast cells that were subjected to 5% hypoxia for 24 h and subjected to different duration of 33 mM high glucose challenge. Further, the involvement of HIF-1α and BNIP3 in cellular damage and the mechanism of protection of TMP were determined by overexpression and silencing HIF-1α and BNIP3 protein expression. The results show that hypoxic effects on cell viability aggravates with high glucose challenge and this augmentative effect is mediated through BNIP3 in H9c2 cardiomyoblast cells. However, TMP administration effectively reversed the augmented HIF-1α levels and BNIP3 elevation. TMP improved the survival of H9c2 cells and effectively suppressed apoptosis in H9c2 cells. Further comparison on the effects of TMP on H9c2 cells challenged with high glucose and those challenged with hypoxia show that TMP precisely regulated the hypoxic intensified apoptotic effects in high-glucose condition. The results clearly show that flavoring agent-TMP attenuates cytotoxicity amplified by hypoxia challenge in high glucose condition by destabilizing HIF-1α.